Teacher and school in Brazilian colonial time - Gilberto Jordão (Journal of Physical Education (Maringá), 2008)
The aim of this paper is to rescue and to search in time the forms and methods used by teachers of Brazilia colonial time. How the province men viewed education and what their main objectives were. It also focuses on teachers’ struggle for worthy eduaction and job.